-27 a^3 c - 6 a^2 x - 2 a b - 30 a + x^3 - 3 x^2 + 25
Объяснение:
Всё легко и просто, вот пошаговая инструкция:
x = -(2^(1/3) (-18 a^2 - 9))/(3 (729 a^3 c + 162 a^2 + sqrt(4 (-18 a^2 - 9)^3 + (729 a^3 c + 162 a^2 + 54 a b + 810 a - 621)^2) + 54 a b + 810 a - 621)^(1/3)) + (729 a^3 c + 162 a^2 + sqrt(4 (-18 a^2 - 9)^3 + (729 a^3 c + 162 a^2 + 54 a b + 810 a - 621)^2) + 54 a b + 810 a - 621)^(1/3)/(3 2^(1/3)) + 1
Или же можешь взять это:
d/dx(x^3 - 3 x^2 - x (6 a^2) - 2 a b - (3 a c) (9 a^2) - 30 a + 25) = 3 (x - 2) x - 6 a^2
37х+29у=1156⇒х=(1156-29у)/37
43х+38у=1438
43*(1156-29у)/37 +38у=1438
49708/37 - 1247/37у+38у=1438
159/37у=3498/37
у=3498/37:159/37=3498/37*34/159=22-стоила бутылка воды
х=(1156-29*22)/37=(1156-638)/37=518/37=14-стоил пирожок